2018
DOI: 10.1177/1934578x1801301239
|View full text |Cite
|
Sign up to set email alerts
|

Eremophilane-type Glycosides: A Mini-Review

Abstract: The occurrence, special aspects of structural determination, biological activities, and potential taxonomic application of eremophilane-type glycosides, a rare group of metabolites from higher plants, are reviewed. This mini review covers the literature published for period 2006 to 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Several hundred eremophilanes have been identified to date, but only a few of these have been isolated in glycosylated forms. 9 Our finding of a new sesquiterpenoid glucoside not only enriched the chemical diversity of glycosylated eremophilane-type natural compounds, but suggested that N. tabacum could be a source of chemically diverse compounds. 13-Hydroxycapsidiol was first isolated from Capsicum frutescens Linn.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…Several hundred eremophilanes have been identified to date, but only a few of these have been isolated in glycosylated forms. 9 Our finding of a new sesquiterpenoid glucoside not only enriched the chemical diversity of glycosylated eremophilane-type natural compounds, but suggested that N. tabacum could be a source of chemically diverse compounds. 13-Hydroxycapsidiol was first isolated from Capsicum frutescens Linn.…”
Section: Resultsmentioning
confidence: 75%
“…2,7 Eremophilane sesquiterpenoids predominantly exist in non-glycosylated forms in plants, and fewer than three dozen eremophilane glucosides have been identified from plants belonging to the Asteraceae and Lauraceae families. 8,9 To the best of our knowledge, only one glycosylated eremophilane sesquiterpenoid from the Solanaceae family has been found thus far. 10 As a result of our current study aimed at the discovery of anti-TMV secondary metabolites and expanding the chemical diversity of Nicotiana tabacum L, a new eremophilane glucoside (1) was isolated and identified from the leaves of Nicotiana tabacum (Solanaceae).…”
Section: Introductionmentioning
confidence: 99%